Implementación de Lógica Difusa para realizar Pruebas de Hipótesis Estadísticas Univariadas - Figueroa García, Juan Carlos; Campos Trujillo, Luis Eduardo; Caquimbo Tabares, Camilo (Ingeniería, 2005)
This paper shows a fuzzy logic approach to univariate statistical hypothesis testing. This tests are an inferential tools to determine whether a statement about the value of a population’s parameter should be rejected or not. Classical statistical techniques used in hypothesis testing have an important limitation, because does not show the fulfillment level of the used sample faced with the population of interest. The fuzzy application wants to offer, to the appraiser of a sample of a population, a value that indicates the fulfillment level of the statement, in order to improve the decisions making about the sample.